Biotechnological Potential of Weizmannia ginsengihumi in the Conversion of Xylose into Lactic Acid: A Sustainable Strategy - Santos, Larissa Provasi [UNESP]; Yoshimura, Ingrid [UNESP]; de Andrade, Fernanda Batista [UNESP]; Contiero, Jonas [UNESP] (MDPI, 2025)
The aim of this study was to isolate Weizmannia spp. that produce lactic acid from xylose and use an experimental design to optimize the production of the metabolite. After isolation, the experiments were conducted in xylose-yeast extract-peptone medium. The identification of isolates was performed using the 16S rDNA PCR technique, followed by sequencing. A central composite rotatable design (CCRD) was used to optimize the concentrations of the carbon source (xylose), nitrogen source (yeast extract and peptone), and sodium acetate. Two strains were considered promising for lactic acid production, with W. coagulans BLMI achieving greater lactic acid production under anaerobic conditions (21.93 ± 0.9 g·L−1) and a yield of 69.18%, while the strain W. ginsengihumi BMI was able to produce 19.79 ± 0.8 g·L−1, with a yield of 70.46%. CCRD was used with the W. ginsengihumi strain due to the lack of records in the literature on its use for lactic acid production. The carbon and nitrogen sources influenced the response, but the interactions of the variables were nonsignificant (p < 0.05). The response surface analysis indicated that the optimal concentrations of carbon and nitrogen sources were 32.5 and 3.0 g·L−1, respectively, without the need to add sodium acetate to the culture medium, leading to the production of 20.02 ± 0.19 g·L−1, productivity of 0.55 g/L/h after 36 h of fermentation, and a residual sugar concentration of 12.59 ± 0.51 g·L−1. These results demonstrate the potential of W. ginsengihumi BMI for the production of lactic acid by xylose fermentation since it is carried out at 50 °C, indicating a path for future studies